Enhancing Numeracy and Literacy Skills of Grade I Pupils through a Parent-Induced Learning Program: Ilaw sa Lilim for Para Teachers Coping with Bereavement (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
Literacy refers to the ability of learners to comprehend, analyze, and creatively construct written and printed materials associated with various contexts, whereas numeracy refers to the ability to analyze and interpret numerical principles (UNESCO). The active involvement and participation of the parents in the education of their child is far greater now in the new normal compared to the previous setting. This study aimed to determine the effectiveness of parent-induced learning, namely